SELF- EFFICACY AMONG LEADERS OF EDUCATION IN THE TECHNOLOGY ERA: A SYSTEMATIC REVIEW - Suzzanna Amir Mohammad; Halimah Mohd Yusof; Siti Norbaya Mohd Radzuan; Noor Idayu Amir Mohammad, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In the technology era, school leaders' self-efficacy plays a pivotal role in shaping educational outcomes. This abstract explores the significance of self-efficacy among school leaders in effectively integrating technology into their institutions, fostering innovation, and improving overall educational practices. This review seeks to synthesize the available knowledge, assess the effectiveness of self- efficacy among school leaders, and highlight critical areas for further research and improvement. This study used PRISMA approach. The systematic search of academic databases using Scopus and Web of Science database yielded a comprehensive selection of studies, reviews, and articles related to self- efficacy and leadership. After applied advanced searching approach using keyword (self- efficacy, education, and leader). The analysis revealed that self- efficacy of leaders played a pivotal role in improving educational management and accomplishment, building up motivation to do better for the institutions. The final finding data is (n=26) which review identified key themes, including the self- efficacy, leadership self- efficacy, and the importance of educators’ motivation. Expert validation decided to divide into three themes which is (1) teacher self- efficacy and educational practice, (2) leadership and self- efficacy and (3) professional development.